(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, the formation of mutual relations between children in the family based on national values and traditions, the importance of further development of our national values in our spiritual and educational work, the fact that the family and values are forever closely connected with each other, the positive level of the family’s attitude towards children is written.